Islamic economic transformation in Pakistan: Prospects, structural impediments, and the imperative of shariah-compliant governance - Waqas Ahmad Watto (PRIVIETLAB, 2026)
Pakistan, the world’s second-largest Muslim-majority nation by population, occupies a uniquely consequential position in the global discourse on Islamic economic thought. Decades after its constitutional declaration as an Islamic republic and the formal promulgation of the Objectives Resolution of 1949, the country’s economic architecture remains deeply entangled with interest-based (riba) financial instruments, structurally asymmetric wealth distribution, and governance frameworks that fundamentally diverge from maqasid al-Shariah, the higher objectives of Islamic law. This opinion article contends that Pakistan’s persistent macroeconomic instability, income inequality, and institutional underdevelopment are not merely technical failures of economic management but, at a deeper analytical level, symptoms of an incomplete and often performative engagement with the foundational principles of Islamic economics. Drawing on scholarship in Shariah-compliant finance, comparative institutional economics, and recent empirical literature on Pakistan’s financial sector, this article examines the structural barriers inhibiting genuine Islamic economic transformation, evaluates the current trajectory of Islamic banking and Zakat administration, critically interrogates the role of the state, and proposes a set of evidence-informed and normatively grounded policy directions. The central argument advanced herein is that a coherent, institutionally embedded embrace of Islamic economic principles, encompassing riba elimination, redistributive instruments such as zakat and waqf, ethical investment frameworks, and participatory finance, offers Pakistan not merely a theological aspiration but a practically viable pathway toward sustainable, equitable, and sovereignty-preserving economic development.